The shortcomings of emergency remote teaching in rural settings of Zimbabwe during COVID-19 school closures: lessons from China’s experience - Nhongo, Raphael; Tshotsho, Baba Primrose (AOSIS, 2022)
Background: In the wake of the coronavirus disease 2019 (COVID-19) pandemic, schools were forced to close indefinitely with no clue as to when they would reopen. Upon school closures, remote teaching was adopted, with online teaching becoming the most preferred mode of instruction, yet the Information Communication Technology (ICT) infrastructure was not adequate enough across the country. Aim: This article scrutinises the remote teaching approaches that were put in place in Zimbabwe in response to the closure of schools during the COVID-19 lockdown. The article investigates how the adopted approaches were suitable for conditions in rural settings. Setting: The study looks at the challenges faced in the implementation of remote teaching during COVID-19 school closures in rural areas of Matabeleland provinces in Zimbabwe. Methods: The study adopted a qualitative phenomenological approach to analyse the teaching approaches that were put in place by the government and other stakeholders. Twenty teachers from 20 rural schools drawn equitably from two provinces, Matabeleland South and Matabeleland North, were interviewed on the shortcomings of these remote teaching approaches. Results: The results revealed that the remote teaching approaches that were put in place excluded learners in rural settings. This is because of the challenges in infrastructure, economic condition and restrictions on remote teaching approaches imposed by the government. Conclusion: As Zimbabwe is facing economic hardships and infrastructure development challenges, it was supposed to adopt emergency remote teaching instead of long-term approaches. A variety of approaches that suit specific physical environments should have been adopted instead of sticking to only one throughout the country.